2004
DOI: 10.1189/jlb.0904486
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the protective and pathologic T cell species in the virus-induced corneal immunoinflammatory condition herpetic stromal keratitis

Abstract: Herpetic stromal keratitis (HSK) results in postinfection with Herpes simplex virus type 1 (HSV-1). The pathogenesis involves tissue damage by the host immune system, classifying HSK as an immunopathological disease. The crucial disease orchestrating cells is thought to be the T lymphocytes. The present study elucidates pathogenic and protective T cell subsets involved in the development of HSK using the gBT mice, which possess a monoclonal population of CD8+ T cells reactive to a HSV immunodominant epitope. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…There were statistically significant reductions of scores for the DKO mice compared to WT mice at 6 and 7 dpi, although the differences were very small (2.0 versus 2.5 at 6 dpi and 2.1 versus 2.7 at 7 dpi), and inflammatory responses resolved by day 16 in both WT and DKO animals. The influx of innate and adaptive immune cells in the cornea influences early control of the infection and virus-induced inflammation (38,39). The total numbers of leukocytes (CD45 ϩ cells) infiltrating the corneas and TG of DKO and WT mice at 3 and 8 dpi were similar ( Fig.…”
Section: Hsv-1-induced Clinical Signs Are Not Mediated By Dok Proteinsmentioning
confidence: 79%
“…There were statistically significant reductions of scores for the DKO mice compared to WT mice at 6 and 7 dpi, although the differences were very small (2.0 versus 2.5 at 6 dpi and 2.1 versus 2.7 at 7 dpi), and inflammatory responses resolved by day 16 in both WT and DKO animals. The influx of innate and adaptive immune cells in the cornea influences early control of the infection and virus-induced inflammation (38,39). The total numbers of leukocytes (CD45 ϩ cells) infiltrating the corneas and TG of DKO and WT mice at 3 and 8 dpi were similar ( Fig.…”
Section: Hsv-1-induced Clinical Signs Are Not Mediated By Dok Proteinsmentioning
confidence: 79%
“…Work from our laboratory and others has shown that the CD8 ϩ T cells are critical for protection against recurrent ocular herpesvirus infection and disease (23,24,39). However, the relative contribution of each of the CD8 ϩ T cell subpopulations in protection against recurrent herpes has not been reported.…”
Section: Discussionmentioning
confidence: 97%
“…In animal models of herpes infection and disease, HSV-specific CD8 ϩ T cells play a critical role in aborting attempts of virus reactivation from latency and in clearing herpetic disease (3,5,(13)(14)(15)(16). However, herpetic corneal disease is also associated with HSV-specific CD8 ϩ T cell responses (17,18).…”
Section: Importancementioning
confidence: 99%